Situating Essentials of ‘Learning to Live Together’ within Pedagogic Practices A Social-Constructivist Perspective - Mishra, Rishabh Kumar (JOURNAL OF INDIAN EDUCATION, 2013)
‘Learning to live together’ has emerged as a major theme of educational practices when Delors Commission (1996) report, considered it as one of the four pillars of learning. Delors Commission has considered education as an indispensible asset in its attempt to attain the ideals of peace, freedom and social justice. Against this backdrop, this paper reports a study conducted under the theoretical backdrop of social-constructivism. In the first section, it explores ‘essentials’ necessary for ‘learning to live together’. The paper explains that as one of the significant agency of socialisation (basically secondary socialisation) education should unfold the internal ‘humanity’. This goal can be achieved only if the sense of ‘togetherness’ and ‘belongingness’ becomes intra-psychic from inter-psychic. The second section of the paper deals with empirical data and analysed pedagogic practices of social science aimed at integrating the essentials of ‘learning to live together’. It was found that pedagogic practices based on social constructivism help to raise social issues, clarify social values and enable learners to develop a sense of ‘living together’. It is argued in the paper that generating a community of learners engaged in discussing social issues is fundamental to social cohesiveness. Differences need to be highlighted in order to appreciate diversity. Crucial social issues need to be discussed in classroom rather than being brushed under the carpet. It is through conflict and discomfort that resolutions are arrived at.